Aboriginal peoples' perspectives about COVID-19 vaccines and motivations to seek vaccination: a qualitative study. Issue 7 (20th July 2022) - Graham, Simon; Blaxland, Megan; Bolt, Reuben; Beadman, Mitchell; Gardner, Kristy; Martin, Kacey; Doyle, Michael; Beetson, Karen; Murphy, Dean; Bell, Stephen; Newman, Christy E; Bryant, Joanne
Abstract : Introduction: Aboriginal and Torres Strait Islander (Aboriginal) people compared with non-Aboriginal people in Australia have higher rates of chronic conditions. These conditions increase the risk of poorer health outcomes if infected with COVID-19, highlighting the importance of COVID-19 vaccination. This study examined what Aboriginal people think about COVID-19 vaccines, reasons why they were vaccinated or not vaccinated and factors involved in receiving COVID-19 vaccination. Methods: We used a participatory peer researcher method to interview 35 Aboriginal people aged 15–80 years living in Western Sydney, Australia. Local Aboriginal people who had ties with the community conducted the interviews. The questions and analyses were framed using the WHO's Behavioural and Social Drivers of COVID-19 model. Interviews occurred between February 2021 and March 2021. Peer researchers were paid for their time in training and to conduct the interviews and each participant received $50. Results: Reasons why participants would seek vaccination included: to protect themselves from infection and severe illness, to protect others in their community, to travel again and to return to 'normal life'. Reasons why some participants were hesitant about being vaccinated included: fear of vaccine side effects; negative stories on social media; and distrust in Australian governments and medical institutions. Aboriginal people preferred to access COVID-19 vaccination through their local Aboriginal Health Service or a general practitioner they already knew. Conclusion: Achieving high vaccination rates in Aboriginal communities is possible if vaccination programmes are delivered through trusted general practitioners or Aboriginal Health Services.